Self-fulfilling risk panics - Philippe Bacchetta; Cédric Tille; Eric van Wincoop (Graduate Institute of International and Development Studies, 2010)
The Recent crises have seen very large spikes in asset price risk without dramatic shifts in fundamentals. We propose an explanation for these risk panics based on self-fulfilling shifts in risk made possible by a negative link between the current asset price and risk about the future asset price. This link implies that risk about tomorrow's asset price depends on uncertainty about risk tomorrow. This dynamic mapping of risk into itself gives rise to the possibility of multiple equilibria and self-fulfilling shifts in risk. We show that this can generate risk panics. The impact of the panic is larger when the shift from a low to a high risk equilibrium takes place in an environment of weak fundamentals. The sharp increase in risk leads to a large drop in the asset price, decreased leverage and reduced market liquidity. We show that the model can account well for the developments during the recent financial crisis.
Keywords: 330; Sunspot; Finanzanalyse; Portfolio-Management; Theorie